Resonating Within the Dynamo: A Phenomenological Exploration of Work Wellbeing Among Millennials in Jakarta's Startup Ecosystem - Dipoatmodjo, Tenri Sayu Puspitaningsih (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This phenomenological study explores the lived experience of work wellbeing among millennial employees within Jakarta’s dynamic technology startup ecosystem. Through in-depth interviews with ten participants across diverse roles and startup stages, the research reveals that well-being transcends traditional financial metrics, emerging instead as contextualized resonance, a state of thriving within the environment’s inherent chaos, speed, and uncertainty. Four interconnected dimensions define this resonance: (1) Meaningful Contribution (alignment with personal values and tangible impact), (2) Autonomy and Flexibility (trust in self-management, albeit challenged by blurred boundaries), (3) Authentic Interpersonal Relationships (psychological safety and communal support as buffers against stress), and (4) Space for Growth (continuous learning and non-linear development pathways). The findings underscore that millennials derive profound satisfaction from co-creating innovation but require deliberate organizational support to mitigate burnout risks. This study advocates for human-centered HR strategies transforming Jakarta’s startup dynamism from a wellbeing challenge into a catalyst for resilience, retention, and holistic fulfillment.